Fatigue Modelling for Stone Mastic Asphalt (SMA) - Muniandy, Ratnasamy; Loong, Tang Eng; Omar, Husaini (Universiti Putra Malaysia Press, 2001)
Fatigue cracking is one of the major distresses found in many asphalt pavements. The premature cracking of the pavements results in the increased annual cost of resurfacing, maintenance and rehabilitation. Generally, any asphalt mix is tested in the laboratory and predictions are made using the performance curves and local conditions. However, in Malaysia there are not any pavement prediction models developed yet that can be used to predict the asphalt mix's fatigue life performance under the local environmental conditions. This paper looks into the fatigue characteristics of SMA by using local materials and environmental conditions. For the purpose of evaluation SMA14 ( SMA with 14mm aggegate as nominal) with 5 different gradations within the JKR's ACW14 gradation envelope were used. The repeated load indirect tensile tests at three different temperatures (30°C, 40°C, 50°C) and five different dynamic loadings (500N, 750N, 1000N, 1250N, 1500N) were carried out under stress controlled mode using the MATTA Machine. The fatigue performance test results plotted on a logarithmic scale of fatigue strain and load repetitions showed a good agreement with the historic trend of the fatigue data. The logarithmic relationship between fatigue loading and strain was evaluated and found to be linear at certain reliability regardless of the testing condition and mix parameter. This indicates that the fatigue model for SMA is a function of asphalt volume, resilient modulus and the fatigue strain values.